TEST RESULTS OF MILKING LINER WITH BACTERIOSTATIC PROPERTIES - Tsoy, Y.; Kirsanov, V.; Filkov, M. (Energy and Automation, 2016)
Tests of milking machines with liners modified ву drug Realm-1. It is found that the surface of the rubber has bacteriostatic effect, it does not cause irritation of the mammary gland and the well wash.